Development of a monolith based immobilized lipase micro-reactor for biocatalytic reactions in a biphasic mobile system - Haswell, Stephen J.; He, Ping; Greenway, Gillian (Process Biochemistry, 2009)
This paper reports a simple method for producing macroporous silica-monoliths with controllable porosity that can be used for the immobilization of lipases to generate an active and stable micro-reactor for biocatalysis. A range of commercially available lipases has been examined using the hydrolysis reactions of 4-nitrophenyl butyrate in water-decane media. The kinetic studies performed have identified that a similar value for k(cat) is obtained for the immobilized Candida antarctica lipase A (0.13 min(-1)) and the free lipase in solution (0.12 min(-1)) whilst the immobilized apparent Michaelis constant K-m (3.1 mM) is 12 times lower than the free lipase in solution (38 mM). A 96% conversion was obtained for the immobilized C. antarctica lipase A compared to only 23% conversion for the free lipase. The significant higher conversions obtained with the immobilized lipases were mainly attributed to the formation of a favourable biphasic system in the continuous flowing micro-reactor system, where a significant increase in the interfacial activation occurred. The immobilized C. antarctica lipase A on the monolith also exhibited improved stability, showing 64% conversion at 80 degrees C and 70% conversion after continuous running for 480 h, compared to 40 and 20% conversions under the same temperature and reaction time for the free lipase.